PERSEPSI PENGGUNA APLIKASI AKUNTANSI MYOB, ZAHIR ACCOUNTING DAN JURNAL DALAM MENYUSUN LAPORAN KEUANGAN - Hermawan, Aditya; Ningsih, Wiwik Fitria (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
This research provides a deep understanding of the experience and preferences of users of accounting applications such as MYOB, Zahir, and Jurnal. In this study, a class action method was used that involved respondents in dealing with examples of cases of preparing financial statements. For this purpose, respondents will use the accounting computer application Zahir Accounting Enterprise Version 6.0, MYOB version 18, and also access the journal through www.jurnal.id. This research involved 79 MSME actors operating in Malang City, East Java Province, and they were divided into three classes. The implementation of Class Actions takes place over a two-month period, starting from April to May 2023. In data analysis, a descriptive statistical analysis method is used that involves manual calculation of the score of each answer given by respondents. It is concluded that each accounting computer application has advantages and disadvantages in certain aspects. Zahir tends to score well in the categories of "Easy to operate on various devices" and "Additional Presentation of Supporting Information that is easy to understand," indicating ease of use across devices and good presentation of information.